Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1108/03090590210428133
|View full text |Cite
|
Sign up to set email alerts
|

Human resource development and workplace learning: emerging theoretical perspectives and organisational practices

Abstract: Workplace learning and HRD are considered legitimate topics for study and investigation alongside organisational strategies and practices. Considers key themes in the workplace earning literature in addition to its relationship with HRD. Identifies a paradigm shift from formalised, intermittent and discontinuous learning to increasingly informal, experiential, asynchronous and real‐time situated learning. Highlights three contemporary themes in both the workplace learning and HRD literatures, namely: knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 28 publications
2
72
0
2
Order By: Relevance
“…Davies, Taylor & Savery, 2001;Nolan, Conway, Farrell & Monks, 2010) support the importance of training in these three areas. Given that line managers are central to the process of workplace learning and in supporting both individual and organisational learning processes (Garavan, Morley, Gunnigle & McGuire, 2002), it is reasonable to investigate their perceptions of HRD.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davies, Taylor & Savery, 2001;Nolan, Conway, Farrell & Monks, 2010) support the importance of training in these three areas. Given that line managers are central to the process of workplace learning and in supporting both individual and organisational learning processes (Garavan, Morley, Gunnigle & McGuire, 2002), it is reasonable to investigate their perceptions of HRD.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…Many traditional terms such as 'staff training and development' and 'work place education' have been used to refer to the set of formal organisational and individual practices designed to enhance the potential contribution of human resources to the organisation (Walton, 1999). In recent years, the terms 'workplace learning', 'human resource development' and 'strategic human resource development' are used to comprehensively explain individual and organisational learning processes (Garavan, 1991;Garavan, Morley, Gunnigle & McGuire, 2002).…”
Section: Hrd In the Hospitality Sector And Destination Competitivenessmentioning
confidence: 99%
“…She asserts that it is effective continuing professional development that is most likely to be an agent for change. Garavan et al (2002) found that work, learning and performance are inextricably linked:…”
Section: Work Learning Performancementioning
confidence: 99%
“…Many researchers have studied facilitator's competencies (Garavan et al 2002;Vreede et al 2002;McFadzean 2002;Clawson and Bostrom 1996;McFadzean and Nelson 1998). Also in practice, facilitator competencies and skills have been investigated by members of the International Association of Facilitators (IAF) as well as the Institute of Cultural Affairs (ICA).…”
Section: Facilitator Competenciesmentioning
confidence: 99%